Corrective Feedback and Learner Uptake in Adult ESL Classrooms - Mikiko Suzuki (Studies in Applied Linguistics & TESOL, 2004)
This article presents a study investigating the relationship between corrective feedback and learner uptake in adult ESL classrooms. Inspired by Lyster and Ranta (1997), the present study describes and analyzes the patterns of corrective feedback and learner uptake, observed in a different context from that of Lyster and Ranta’s study. The database consists of 21 hours of interaction between three ESL teachers and thirty-one adult ESL students. The interaction was audiotaped and transcribed, and then coded according to Lyster and Ranta’s corrective discourse model. The results show both similarities and differences to those in Lyster and Ranta’s study. While the distribution of types of corrective feedback following learner errors showed no major difference from that reported by Lyster and Ranta, the ratio of uptake following certain corrective feedback types greatly differed from their results. Possible accounts for the differences in the results are discussed from the aspects of the classroom setting, students’ ages and their motivation of participating in the language learning programs, teachers’ experience, and the target language.